Survey on research progress for compute first networking - Qingmin JIA; Rui DING; Hui LIU; Chen ZHANG; Renchao XIE (网络与信息安全学报)
With the development of 5G and mobile Internet technology, cloud computing, edge computing and intelligent terminal devices have been developed rapidly.Computing resources indicate a trend of ubiquitous deployment.How to use ubiquitous computing resources efficiently and collaboratively has become a hot topic at present in network field.In this context, the concept of compute first networking (CFN) has been proposed and attracted wide attention.Its basic idea is to enhance utilization of computing resources and improve user experience of network services, by converging computing and network deeply as well as coordinating distributed computing resources.Firstly the background and research status of CFN were analyzed, and then basic structure, workflow, and key technologies about CFN were explicated.Finally, future research directions and challenges about CFN were summarized.